Runway Pavement Strength Evaluation of Yogyakarta International Airports with COMFAA 3.0 Software - Rahmawati, Anita; Rahmawati, Fajar (International Journal of Integrated Engineering, 2022)
Yogyakarta International Airport (YIA) is a new airport which serves as an international transit station for Yogyakarta and surrounding areas. The airport was designed to serve large and heavy aircrafts with relatively high frequency. To meet flight safety standards, the runway must be designed to be able withstand the wheel weight of aircrafts to be served by the airport. The study aims to determine the thickness and strength of the runway pavement using the FAA method (Federal Aviation Administration) and COMFAA software. The reference aircraft used was Boeing 747-400ER based on landing wheel configuration. With a subgrade CBR value of 6%, Aircraft Classification Number (ACN) and Pavement Classification Number values of 77.8 and 94.9, respectively, were obtained. PCN value higher than ACN value indicates that the pavement structure condition is able to withstand the weight of all aircraft types that are planned to be served by the runway of YIA.